2015
DOI: 10.7243/2055-091x-2-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of topical aloe vera on the process of healing of full-thickness skin burn: a histological and immunohistochemical study

Abstract: Background: Skin burn is common universal problem that may lead to ugly scarring, serious handicapping. Availability of natural biological treatment to improve its outcome becomes concern of many researchers. Aim of study: To explore the effect of aloe vera on the angiogenesis process during healing of a fullthickness experimental skin burn. Materials and methods: Seventy rats were divided into three groups; control group (A), group B and group C. Group B was exposed to full-thickness (FT) skin burn. Group C w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 41 publications
5
14
0
Order By: Relevance
“…Wet dressings can double the speed of wound healing because the wet environment allows fibroblast cells to immigrate faster to the epidermis and accelerate the recovery process (33). Aloe Vera also has lysine; lysine helps with wound healing by removing toxic substances, increasing blood flow and removing dead cells (34). The results of this study are consistent with the conclusion of a review study that showed that Aloe Vera gel accelerates burns recovery in superficial grade one burns (35).…”
Section: Discussionsupporting
confidence: 89%
“…Wet dressings can double the speed of wound healing because the wet environment allows fibroblast cells to immigrate faster to the epidermis and accelerate the recovery process (33). Aloe Vera also has lysine; lysine helps with wound healing by removing toxic substances, increasing blood flow and removing dead cells (34). The results of this study are consistent with the conclusion of a review study that showed that Aloe Vera gel accelerates burns recovery in superficial grade one burns (35).…”
Section: Discussionsupporting
confidence: 89%
“…Aloe vera is a native plant in Africa and is so called lily of the desert or the plant of immortality. The Aloe vera extract has some beneficial properties which can decrease inflammation; enhance mature granulation tissue and resulting in help to accelerate wound healing [16]. It also decreases the blood glucose which can be beneficial in diabetic wounds [17].…”
Section: Aloe Veramentioning
confidence: 99%
“…Because Aloe vera extract contains tannic acid and a type of polysaccharide [19] that help wound healing process. Aloe vera extract shows beneficial effects on wound healing by decreasing the inflammatory phase and supplying more mature granulation tissue which finally promotes healing and may be caused to produce a sound well-remodeled scar [16]. The Aloe vera leaf gel has beneficial effects on wound healing by antioxidant properties which can be attributed to some compounds including indoles, and alkaloids [20].…”
Section: Aloe Veramentioning
confidence: 99%
“…Regarding Aloe Vera healing effect on skin, it induces collagen cross linking and hyaluronic acid and dermatan sulfate production through stimulation of growth factor receptors of fibroblast cells [12] which will result in wound contraction as well as improving granulation tissue formation [1]. Moreover, corneal re-epithelialization was reported as a consequence of topical Aloe Vera Gel [14].…”
Section: Introductionmentioning
confidence: 99%
“…Disaster occurs when burn leaves disability on its path besides affecting patients' mental, psychological, and physiological conditions [1].…”
Section: Introductionmentioning
confidence: 99%